Current status and challenges of immunotherapy in ALK rearranged NSCLC - Qi, Rongbin; Yu, Yingying; Shen, Mo; Lv, Dongqing; He, Susu (Frontiers in Oncology, 2022)
Rearrangements of the anaplastic lymphoma kinase (ALK) gene account for 5-6% in non-small cell lung cancer (NSCLC). ALK rearranged NSCLC is sensitive to ALK tyrosine kinase inhibitors (TKIs) but prone to drug resistance. Meanwhile, ALK rearranged NSCLC has poor response to single immunotherapy. Here we mainly describe the immune escape mechanisms of ALK mutated NSCLC and the role of related biomarkers. Additionally, we collate and evaluate preclinical and clinical studies of novel immune combination regimens, and describe the prospects and perspectives for the in vivo application of novel immune technologies in patients with ALK rearranged NSCLC.